KESANTUNAN BERBAHASA GURU KELAS XI SMA NEGERI 1 LIRIK DALAM PEMBELAJARAN - Pertiwi, Tri Yuliana Ayu; Sinaga, Mangatur; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
ABSTRACT: This study discusses the language politeness of Class XI Teachers at Senior High School 1 Lirik in teaching and learning process. This study also discusses the compliance andviolation of politeness principles according to of Leech's politeness principle. Politeness principle is divided into six maxims. The obedience and violation of the principle of politeness is taken from the teacher's speech during teaching and learning process. The compliance and violation of the principle of language courtesy found in the study consisted of the maxims of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, the maxim of agreement, and the maxim of conclusions. This research uses qualitative approach and descriptive method that aims to describe the teacher's speech in the process of learning in the classroom. The results of this study in the form of description of the teacher's speech based on compliance and violation of the principle of language politeness.Keywords: Speech Language, politeness maxims, teacher’s utterances